2017
DOI: 10.1242/bio.024844
|View full text |Cite
|
Sign up to set email alerts
|

How does oestradiol influence the AVT/IT system in female round gobies during different reproductive phases?

Abstract: In this in vitro gradient perfusion study, we determined whether there is a functional relationship between oestradiol and the arginine vasotocin/isotocin (AVT/IT) system in the female round goby (Neogobius melanostomus). Brain explants were perfused in medium supplemented with 17β-oestradiol (E2) at doses mimicking the plasma levels of this hormone in nature during the spawning-capable phase and regressing phase. We aimed to establish which pathway, genomic or non-genomic, is involved in this mechanism in dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 91 publications
(122 reference statements)
0
8
0
Order By: Relevance
“…The results show that high Avp levels correlate with pre-spawning period whereas the highest Oxt levels correspond to spawning. In female round gobies, these increases appear, at least in part, to be dependent on estrogens acting via genomic (nuclear receptors), and genomic and non-genomic mechanisms in the case of Avp and Oxt, respectively ( 98 ). This suggests that season-dependent gonadally-derived positive sex steroid feedback mechanisms may reinforce the seasonal activation of hypothalamic nonapeptide systems.…”
Section: External and Internal Reproductive Cues Regulate Teleost Cen...mentioning
confidence: 99%
See 1 more Smart Citation
“…The results show that high Avp levels correlate with pre-spawning period whereas the highest Oxt levels correspond to spawning. In female round gobies, these increases appear, at least in part, to be dependent on estrogens acting via genomic (nuclear receptors), and genomic and non-genomic mechanisms in the case of Avp and Oxt, respectively ( 98 ). This suggests that season-dependent gonadally-derived positive sex steroid feedback mechanisms may reinforce the seasonal activation of hypothalamic nonapeptide systems.…”
Section: External and Internal Reproductive Cues Regulate Teleost Cen...mentioning
confidence: 99%
“…This regulation also appears to be indirect, as androgen receptor expression was not found in Oxt neurons but on kisspeptin neurons known to stimulate Oxt neurons in this species ( 131 , 135 ). In female round gobies, circulating E 2 levels are higher in the spawning phase compared to non-spawning phase and coincide with high circulating Avp and Oxt concentrations ( 98 ). Brain explant exposure to E 2 in spawning and non-spawning phases stimulated Avp and Oxt release in this species; however, pharmacological studies using the estrogen receptor (ER) antagonist fulvestrant and the transcription inhibitor actinomycin D showed that the effect of E 2 on Avp and Oxt release was mediated by different signaling pathways ( 98 ).…”
Section: Reproductive Function Of Nonapeptides In Teleost Fishesmentioning
confidence: 99%
“…This suggests that in females, AVT production may be associated with physiological status and egg development, ovulation, and steroid hormone production. Further, in female round gobies, perfusion with 17β‐estradiol over explanted brains increased AVT release, and acted through both genomic and nongenomic pathways (Kalamarz‐Kubiak et al, 2017), and gonadal steroids, particularly estrogens, mediate AVT production and expression across taxa (Boyd, 1994; Miller et al, 1989; Sladek & Somponpun, 2008). Gravid, ready‐to‐spawn A .…”
Section: Discussionmentioning
confidence: 99%
“…While many studies documented the presence or absence of sexually dimorphic AVT expression and immunoreactivity, these studies have largely grouped females into a single category while separating males by reproductive or social status. However, gonadal steroids, especially estradiol help maintain and regulate AVT/AVP levels in the brains of fishes, amphibians, and mammals (Boyd, 1994; Kalamarz‐Kubiak, Gozdowska, Guellard, & Kulczykowska, 2017; Miller, Urban, & Dorsa, 1989; Sladek & Somponpun, 2008), suggesting that female reproductive state regulates AVT expression and production. Thus, it is important to examine plasticity of the AVT system in females, as they also undergo cyclical changes in behaviors (aggressive, reproductive, parental) and reproductive physiology comparable to males in many species.…”
Section: Introductionmentioning
confidence: 99%
“…Plasma E 2 was measured using RIA kit (ESTR-CTRIA, Cisbio Bioassays, Codolet, France) without preceding extraction procedure according to the manufacturer’s protocol validated in our laboratory (Kalamarz-Kubiak et al 2017 ; Guellard et al 2019 ). E 2 iodinated with 125 I was used as a tracer.…”
Section: Methodsmentioning
confidence: 99%